2019
DOI: 10.1371/journal.pone.0199408
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: A review to formulate a conceptual framework for coaching as a disability accommodation

Abstract: Although dyslexia affects 5–8% of the workforce this developmental disorder has not been sufficiently researched in adult populations. Yet a diagnosis confers legal protections as employers must provide disability ‘accommodations’ to assist work functioning and performance. The implementation of such accommodations, including coaching, lacks theoretical framing and evaluations of impact in practice. Recognizing a need for conceptual work, we undertook a narrative, systematic scoping review from a realist pragm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 140 publications
(177 reference statements)
0
22
0
Order By: Relevance
“…Over-reliance on heuristical guidance must be addressed by the research communities, and requires collaboration within applied psychological sub-disciplines, occupational therapy, occupational medicine and human resources departments. The limited evidence that does exist broadly supports the implementation of adjustments 64 , 74 , 77 , 80 , 81 but, without sophistication, we are unable to speak to quality control, return on investment or predict which type will work for different individuals/roles. Intensive personalized employment support (IPS) such as that provided to autistic people with multiple needs and people with moderate mental health conditions have found that the benefits only outweigh the costs when wider community measures such as housing and health costs are factored in.…”
Section: Occupational Considerations Of Neurodiversitymentioning
confidence: 95%
See 1 more Smart Citation
“…Over-reliance on heuristical guidance must be addressed by the research communities, and requires collaboration within applied psychological sub-disciplines, occupational therapy, occupational medicine and human resources departments. The limited evidence that does exist broadly supports the implementation of adjustments 64 , 74 , 77 , 80 , 81 but, without sophistication, we are unable to speak to quality control, return on investment or predict which type will work for different individuals/roles. Intensive personalized employment support (IPS) such as that provided to autistic people with multiple needs and people with moderate mental health conditions have found that the benefits only outweigh the costs when wider community measures such as housing and health costs are factored in.…”
Section: Occupational Considerations Of Neurodiversitymentioning
confidence: 95%
“…Many neurominority employees find themselves in need of disability accommodation at work. 63 , 64 Irrespective of legal protection, social and occupational exclusion are endemic for neurominorities. Studies vary in the percentages quoted, yet there is persistent evidence of disproportional representation within prison populations, 64–67 long-term unemployment 32 , 68–70 and failure to achieve career potential.…”
Section: The Biopsychosocial History Of Neurominoritiesmentioning
confidence: 99%
“…We then filtered results by abstract screening, removing any papers without reference to We did not explicitly seek to apply a rigorous quality check at this stage mainly because the aim of the review was not meta-analysis of an intervention success, simply exploration of the extent of research. Instead, we considered the hierarchy of evidence principles (Rousseau et al, 2008) and used quality guidance from related systematic reviews (Doyle and McDowall, 2019;Rojon et al, 2011) to rate papers as strong evidence (systematic review and metaanalysis), medium evidence (well-constructed primary papers) or weak evidence (poorlyconstructed papers, case studies, practitioner opinion and anecdotal evidence). The primary author performed these ratings, the second author cross-checked and discussion was held to resolve conflicts until full consensus was reached.…”
Section: An Empty Review Of Neurodiversity Researchmentioning
confidence: 99%
“…Before the present study, pilot research using longitudinal dyad data from dyslexic coachees and their respective workplace supervisors provided some evidence that both parties perceived improved work performance [ 36 ]. The results of a systemic narrative review of the literature related to improving contextualized work performance via coaching also suggested support for the practice [ 37 ] which we now briefly describe in order to explain the potential for individualized pathways in intervention progress.…”
Section: Introductionmentioning
confidence: 99%
“…An expert consultation process undertaken as part of the narrative systematic review protocol [ 37 ] highlighted that several cognitive and psychosocial mechanisms are specifically relevant to improving the work performance of dyslexic adults. These could be considered the basis for an intervention to ‘work’, as per the personalized pathways predicted in applied psychology.…”
Section: Introductionmentioning
confidence: 99%